Application of BEM in interface debonding of composite - Qinye Lin; Yongqiang Chen (2015)
The debonding of particle/matrix interfaces has an important effect on the behavior of composite materials. During last decades, great efforts have been made to simulate the behavior of the interface. Boundary element method, as an alternative effective numerical method, has great advantages in simu...
Keywords: BEM; composite; inclusion; Interface debonding; Master-Slave Elimination